Q & A voices from queer Asian North America - Manalansan, Martin F. IV. 1960-; Hom, Alice Y. 19XX-; Fajardo, Kale Bantigue Prof (Temple University Press, 2021)
"This book offers a vibrant array of contemporary Asian North American LGBT scholarship and cultural productions from essays, poetry, visual art, and memoirs of activists and scholars"--
This book is a follow-up to Q & A: Queer in Asian America edited by David L. Eng and Alice Y. Hom, published in 1998
Keywords: Asiaten; LGBT; Queer-Theorie; Nordamerika; Asian American gays / Social conditions; Asian American lesbians / Social conditions; Asian American bisexuals / Social conditions; Gays / North America / Identity; Lesbians / North America / Identity; Transgender people / North America / Identity; Bisexuals / North America / Identity; Queer theory; Gays / Identity; Lesbians / Identity; Transgender people / Identity; North America; Aufsatzsammlung